MacWilliams Identity for m-spotty Hamming Weight Enumerator Over the Ring $\mathbb{F}_2+v\mathbb{F}_2$ (European Journal of Pure and Applied Mathematics, 2012)
The m-spotty byte error control codes can correct or detectmultiple spotty byte errors that are distributed in multiplebytes. These codes are successfully applied to computer memorysystems that use RAM chips with $b$-bit Input/Output data whenhigh-energy particles strike a particular RAM chips. In thispaper, we derive a MacWilliams type identity for m-spotty Hammingweight enumerator over the ring $\mathbb{F}_2+v\mathbb{F}_2$ with$v^2=v.$